Implementasi Web Service Pada Sistem Rekam Medis Terpusat - Bahtyar Bahtyar; Nurudin Santoso; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The recording of medical records is generally written and stored in each health facility unit to maintain the privacy of the patient's health information. Displacement of patient treatment at health facility resulted in new health facility must be perform patient data rechecking. If in an emergency this condition will reduce the patient's emergency response time. The centralized of medical record system will bridge the limitations of this information. By utilizing REST technology the web service system can process and store information centrally. So it is expected that the records of medical record patient's from previous health facilities can be known. From white box testing that is by unit testing of centralized medical record system get result 87,5%, while for testing blackbox with validation test get 100% result. Web service testing is done using the Postman Application to test methods on services such as GET, POST, PUT and DELETE and yields a 100% success rate. Based on the average total percentage of successful functional testing if the conversion into predicate table of functional suitability feasibility of the system developed declared as very good.